Evaluation of biological fluid analysis using the sysmex XN automatic hematology analyzer. Issue 5 (31st August 2017) - Aguadero, Vicente; Cano‐Corres, Ruth; Berlanga, Eugenio; Torra, Montserrat
Abstract : Background: Hematological cytometers with a biological fluid module could potentially correct the limitations of the manual chamber method. This study evaluates the agreement between the manual technique and the Sysmex XN‐1000 analyzer for white blood cell (WBC) and red blood cell (RBC) counts, as well as for leukocyte differentiation in different types of fluids. This study also evaluates the advantages of incorporating the technique in routine laboratory work. Methods: One hundred and three fluid samples examined were 45 ascite (AF), 21 synovial (SF), 33 pleural (PF), and 31 cerebrospinal (CSF) fluid samples. All cell counting was performed with a Sysmex XN‐1000 and a Fuchs‐Rosenthal counting chamber. May Gründwald‐Giemsa stain was used for manual WBC differentiation. The manual analysis data were obtained in duplicate by the same two observers. Passing‐Bablok regression and the Kappa index were used to evaluate the interchangeability and concordance. Results: Good agreement was observed for WBC differentiation in all fluids and for WBC counts in SF and PF. An optimal Kappa index was obtained, which indicated agreement and clinical significance for WBC and RBC counts in CSF and for RBC counts in PF. There was disagreement for WBC and RBC analysis in AF, with significantly higher results from the Sysmex XN‐1000 than from the manual method. A reduction in laboratory response time was observed when using the automatic method. Conclusions: Except for AF, the Sysmex XN‐1000 results agree with those of the manual method, although to different degrees depending on the fluid type. © 2017 International Clinical Cytometry Society